Ultra-wideband (UWB) microwave imaging for breast cancer detection : UWB experiments on breast phantoms - Lai, Joshua Chong Yue (2010)
The potential of UWB breast cancer detection has been demonstrated with simple experiments on homogenous breast phantoms which do not represent the tissue dielectric properties of heterogeneous human breast. This thesis attempts to bridge the gap by conducting experiments on pulse-based UWB microwave breast imaging with realistic tissue mimicking breast phantoms. Experimental issues which are important for the development of pulse-based UWB breast cancer detection prototype and the compensation methods are studied. These includes pulse instability, loss compensation, narrowband frequencies interference, limited dynamic range, phantom positioning error, averaging number and antenna number. Detection capability is shown to be significantly improved by the compensation methods. The breast phantoms used in the experiments are realistic and comparable to human breast in term of dielectric properties. Unlike previously reported experiments that use lower (compared to human breast tissue) dielectric homogeneous materials as the breast medium, the experiments are significantly different in two ways. Firstly, dielectric loss and dielectric constant of the breast phantoms used in our experiments are close to actual human breasts. Secondly, heterogeneous breast phantoms are fabricated by mixing phantom materials of different dielectric constants to simulate the glandular tissue clutters in adipose tissue matrix of the human breast. More realistic experiments are designed based on the new results from large scale dielectric measurements on normal and malignant breast tissues. Extensive experiments are conducted to simulate the wide variability in dielectric properties of human breast. Experiment results show that the experimental setup is capable of detecting 2 mm tumor in breast phantoms.